KELIMPAHAN GASTROPODA DI SUNGAI KAMPAR KANAN KELURAHAN AIR TIRIS KECAMATAN KAMPAR - Gustika Yuli Yendri; Nur El Fajri; Muhammad Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
In the Kampar River there are activities that affect the water quality in general and affect the abundance gastropoda. To understand the abundance of gastropoda in that river, a study has been conducted in February to March 2017. Parameters meansured were types and abundance of gastropoda, temperature, depth, turbidity, current speed, pH, dissolved oxygen, COD and BOD5 concentration. Sampling were conducted 3 times, once/week, in 5 statiun. Relationship between gastropoda abundance and organic material content was analyzed using a simple linear regression. Result shown that there were 6 gastropoda spesies present, namely Melanoides granifera (20/m2), Melanoides tubercullata (120/m2), Bellamya sp (45/m2), Brothia sp (28/m2), Pila ampullacea (25/m2) and Thiarascabra(4/m2). Organic material content in the sediment was 21.2-73.05%. While the type of sediment fractions that dominate the waters of theKamparRiver is sand and gravel. There was strong relationship between gastropoda abundance and organic material content (96%).Keywords:Makrozoobentos,Melanoides tuberculata, Organic Matter,Sediment Fraction, Kampar River